2017
DOI: 10.3839/jabc.2017.027
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of proximate compositions, antioxidant, and antiproliferative activities between blueberry andSageretia thea(Osbeck) M.C.Johnst fruit produced in Jeju Island

Abstract: This study was aimed to evaluate and compare the proximate composition, antioxidant and antiproliferative activities of Sageretia thea (Osbeck) M.C.Johnst (S. thea) fruit and blueberry. The calorific value, crude protein, crude fat, crude ash, and carbohydrate were higher in S. thea fruit than in blueberry. S. thea fruit and blueberry have different profile of free sugars, in which amounts of fructose, glucose, and maltose were much higher in S. thea fruit than in blueberry. The methanol extracts of S. thea fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 48 publications
0
1
0
2
Order By: Relevance
“…국내에서는 강 원도와 함경도, 그리고 한라산 능선 지역에서 생산되고 있 다. 댕댕이나무에 관한 연구로는 항산화 활성 및 성분 분 석에 대한 연구가 진행 되었고 [8,9] 알코올성 손상 간기능 개선 효과에 대한 연구 [10] 면역 [11], 항암 [12]등에 효과 적이며 특히 항산화 효과는 방사선 치료 시 회복에 도움을 주는 것으로 보고되었다 [13,14]…”
unclassified
“…국내에서는 강 원도와 함경도, 그리고 한라산 능선 지역에서 생산되고 있 다. 댕댕이나무에 관한 연구로는 항산화 활성 및 성분 분 석에 대한 연구가 진행 되었고 [8,9] 알코올성 손상 간기능 개선 효과에 대한 연구 [10] 면역 [11], 항암 [12]등에 효과 적이며 특히 항산화 효과는 방사선 치료 시 회복에 도움을 주는 것으로 보고되었다 [13,14]…”
unclassified
“…The fruits of S. thea were similar in colour to the blueberry, one of the representative berries, and are about twice as small as a blueberry. However, it has been reported that the fruits of S. thea have higher bioactive and nutritional content than blueberry (Ko et al, 2017). In contrast to the leaves and branches of S. thea that have been used for medicinal purposes, the fruits of S. thea have been used primarily for edible purposes, and recently have been reported to exhibit whitening activity via protein kinase B (AKT)/ glycogen synthase kinase-3 beta (GSK3β) signalling pathway (Ko et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…제주산 과일 또는 채소의 항산화 효과에 관한 연구는 '제 주산 진귤, 하귤, 온주밀감의 항산화 활성 비교 (Hyon et al 2010)', '제주산 참다래의 품종 및 숙도에 따른 항산화 활성 비교 (Oh et al 2011)', '제주산 청귤의 착즙액, 착즙박, 원물의 항산화 및 항균 활성 비교 (Choi et al 2019)', '제주산 블루베 리와 상동열매의 일반성분, 항산화 및 항증식 활성 비교 (Ko et al 2017)', '제주산 당근과 벨기에산 파스닙의 항산화 활성 비교 (Park et al 2022)' 등 다양하게 진행되고 있다. 한편, 현재 까지 제주 물 산업 연구는 '제주 물의 기능성 및 혼합음료 개 발 설정에 관한 연구 (Ko et al 2011)', '삼다수의 당뇨병 치료 효과 (Koh et al 2013)' 등 삼다수의 우수성에 관한 연구가 진 행되었다.…”
unclassified